2016
DOI: 10.1021/acsami.6b05830
|View full text |Cite
|
Sign up to set email alerts
|

SiNx Coatings Deposited by Reactive High Power Impulse Magnetron Sputtering: Process Parameters Influencing the Nitrogen Content

Abstract: Reactive high power impulse magnetron sputtering (rHiPIMS) was used to deposit silicon nitride (SiNx) coatings for bio-medical applications. The SiNx growth and plasma characterization were conducted in an industrial coater, using Si targets and N2 as reactive gas. The effects of different N2-toAr flow ratios between 0 and 0.3, pulse frequencies, target power settings and substrate temperatures on the discharge and the N content of SiNx coatings were investigated. Plasma ion mass spectrometry shows high amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…44 In our previous study we found that the SiN x coatings were amorphous 12 hence, the latter applies for the here investigated coatings.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…44 In our previous study we found that the SiN x coatings were amorphous 12 hence, the latter applies for the here investigated coatings.…”
Section: Resultsmentioning
confidence: 57%
“…6(a)-6(d) for different power and frequency settings. Although, ion energies are generally lower in processes using f N 2 =Ar of 0.28 due to the temporarily poisoned target and N 2 dissociation, ionization as well as excitation, 12 the results in Figs. 6(a)-6(d) suggest higher energies and amounts of ions as the average target power (cf.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations